A surface with a biomimetic micropattern reduces colonization of Mycobacterium abscessus. Issue 1 (1st November 2014) - Kim, Eun; Kinney, William H.; Ovrutsky, Alida R.; Vo, Danthy; Bai, Xiyuan; Honda, Jennifer R.; Marx, Grace; Peck, Emily; Lindberg, Leslie; Falkinham, Joseph O.; May, Rhea M.; Chan, Edward D.
Abstract: Nontuberculous mycobacteria (NTM) are ubiquitous organisms found in soil, water, and biofilms. Engineered surface topography has been proposed as a method to reduce microbial biofilm formation. The Sharklet ® micropattern silicone surface has been shown to reduce biofilm formation of pyogenic bacteria. We hypothesized that this micropattern surface will also reduce colonization by Mycobacterium abscessus, a human pathogen. Smooth and micropattern silicone samples were incubated with 1 × 10 6 M. abscessus mL −1 for 2 and 4 days. After processing to optimize recovery of adhered mycobacteria, there was a 75% and 50% reduction in the number of viable M. abscessus recovered from the micropattern surfaces compared to the smooth surfaces at 2 and 4 days after inoculation, respectively. Ziehl–Neelsen staining after measures to remove the adherent microorganisms revealed fewer residual M. abscessus on the micropattern samples as compared to smooth samples, validating the quantitative culture results. Microscopic observation of 2, 4, and 8 day M. abscessus cultures on micropattern samples showed that the organisms preferentially colonized within the channels between the rectangular features. In summary, a micropattern surface reduces the colonization of a pathogenic NTM. It remains to be seen whether this micropattern can reduce infections in humans. Abstract : A surface with a biomimetic micropattern reduces colonization of Mycobacterium abscessus . Abstract :